Functional roles of Ca(v)1.3, Ca(v)3.1 and HCN channels in automaticity of mouse atrioventricular cells Insights into the atrioventricular pacemaker mechanism - Marger, Laurine; Mesirca, Pietro; Alig, Jacqueline; Torrente, Angelo; Dubel, Stefan; Engeland, Birgit; Kanani, Sandra; Fontanaud, Pierre; Striessnig, Joerg; Shin, Hee-Sup; Isbrandt, Dirk; Ehmke, Heimo; et al. (TAYLOR & FRANCIS INC, 2011)
The atrioventricular node controls cardiac impulse conduction and generates pacemaker activity in case of failure of the sino-atrial node. Understanding the mechanisms of atrioventricular automaticity is important for managing human pathologies of heart rate and conduction. However, the physiology of atrioventricular automaticity is still poorly understood. We have investigated the role of three key ion channel-mediated pacemaker mechanisms namely, Ca(v)1.3, Ca(v)3.1 and HCN channels in automaticity of atrioventricular node cells (AVNCs). We studied atrioventricular conduction and pacemaking of AVNCs in wild-type mice and mice lacking Ca(v)3.1 (Ca(v)3.1(-/-)), Ca(v)1.3 (Ca(v)1.3(-/-)), channels or both (Ca(v)1.3(-/-)/Ca(v)3.1(-/-)). The role of HCN channels in the modulation of atrioventricular cells pacemaking was studied by conditional expression of dominant-negative HCN4 channels lacking cAMP sensitivity. Inactivation of Ca(v)3.1 channels impaired AVNCs pacemaker activity by favoring sporadic block of automaticity leading to cellular arrhythmia. Furthermore, Ca(v)3.1 channels were critical for AVNCs to reach high pacemaking rates under isoproterenol. Unexpectedly, Ca(v)1.3 channels were required for spontaneous automaticity, because Ca(v)1.3(-/-) and Ca(v)1.3(-/-)/ Ca(v)3.1(-/-) AVNCs were completely silent under physiological conditions. Abolition of the cAMP sensitivity of HCN channels reduced automaticity under basal conditions, but maximal rates of AVNCs could be restored to that of control mice by isoproterenol. In conclusion, while Ca(v)1.3 channels are required for automaticity, Ca(v)3.1 channels are important for maximal pacing rates of mouse AVNCs. HCN channels are important for basal AVNCs automaticity but do not appear to be determinant for beta-adrenergic regulation.